Household Money Holdings in the Euro Area: an explorative investigation - Franz Seitz; Julian von Landesberger (Journal of Banking and Financial Economics)
In this paper we analyse household holdings of the broad monetary aggregate M3 in the euro area from 1991 until 2009. Households are the largest money-holding sector in the euro area. We develop four models, two in nominal, two in real terms, with satisfactory economic and statistical properties. The main determinants are a transactions variable, wealth considerations, opportunity costs and uncertainty. In particular housing wealth is found to play an important role. The models are robust to different estimation strategies, samples considered and a multitude of misspecification tests. According to our analysis, it is quite apparent that in equilibrium, households jointly determine consumption and broad money holdings which are both influenced by wealth as well as interest rates. The importance of household money holdings for consumption expenditures may cast doubt on a purely passive role for money.